Risk Factors for Recurrent Shoulder Dislocation Arthroscopically Managed with Absorbable Knotless Anchors. (25th November 2014) - Russo, Raffaele; Cautiero, Fabio; Della Rotonda, Giuseppe
Abstract : Purpose . To evaluate the clinical outcome and risk factors for recurrent dislocation after arthroscopic stabilization with absorbable knotless anchor. Methods . We treated 197 patients affected by anterior shoulder instability, either traumatic or atraumatic with the same arthroscopic suture technique. We recorded age at surgery and number and type of dislocations (traumatic/atraumatic). Of the 197 patients, 127 (65.4%) were examined with a mean follow-up of 5.6 years (range: 25–108 months). Eighty-one shoulders were evaluated with the Rowe score and 48 with the Simple Shoulder Test (SST). Results . The mean Rowe score was 90.8, while the mean SST score was 10.9. Recurrence occurred in 10 cases (7.7%) but only in 4 cases was atraumatic, which reduces the real recurrence rate to 3.1%. Patients with recurrence were significantly younger at surgery than patients who did not relapse (P = 0.040 ). Moreover, neither the number (P = 0.798 ) nor the type of shoulder instability (P = 0.751 ), or the amount of glenoid bone loss (P = 0.184 ) significantly affected the probability of recurrence. Conclusions . In a patient population with involuntary monodirectional anterior shoulder instability, use of absorbable knotless anchor was reliable and resulted in a good outcome. In this series the statistical significant risk factors for recurrent dislocation were age of patient.